2015
DOI: 10.5530/pj.2015.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and metal chelating activities of Lagenaria siceraria (Molina) Standl peel, pulp and aerial parts in relation to their total phenol and flavonoid content

Abstract: Objective: The aim of the present study was to evaluate the antioxidant activity and total phenol and flavonoid content of different parts (peel, pulp and aerial parts) of Lagenaria siceraria. Method: Successive extraction was done by cold percolation method using solvents of different polarity viz. petroleum ether, toluene, ethyl acetate, acetone, water. Total phenol content was determined by Folin-Ciocalteu's reagent method and flavonoid was determined by aluminium chloride colorimetric method. The antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In the present study, the maximum TPC was in polar solvent extracts as also reported by Ammar et al [26] and Chanda et al [27] and the maximum TFC was in ethyl acetate extracts. Padalia et al [28] also reported the maximum flavonoid content in ethyl acetate extracts of different flowers.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the maximum TPC was in polar solvent extracts as also reported by Ammar et al [26] and Chanda et al [27] and the maximum TFC was in ethyl acetate extracts. Padalia et al [28] also reported the maximum flavonoid content in ethyl acetate extracts of different flowers.…”
Section: Discussionsupporting
confidence: 90%